Ecological Principles in Utilizing Mangrove Forest as an Ecotourism Area in Tagalaya Vilage, North Halmahera (Agrikan Jurnal Agribisnis Perikanan, 2024)
This research is: a) determine the condition and biodiversity of mangrove forests in Tagalaya Village; b) analyse the application of ecological principles in mangrove forest management; c) analyse the ecotourism potential of Tagalaya Village. d) Develop alternatives to overcome challenges and opportunities for the use and development of mangrove forest-based ecotourism in Tagalaya Village. Data analysis uses a tourist attraction evaluation analysis based on the 1993 Regulation of the Directorate General of PHPA on Tourism Area Potential Evaluation Criteria to assess the ecotourism potential of Tagalaya village. Policy analysis using Analytical Hierarchy Process (AHP) methodology. The results showed that of the 10 criteria for assessing tourist attractions, there were three criteria (30%) that were not feasible as ecotourism areas, with the highest percentage of indicators. The value is 92.5% of the ‘Clean water’ criterion and the minimum value for the ‘Accommodation’ criterion is 10%. The main priority of the criteria supporting the standard utilisation of mangrove forests in Tagalaya Village is clean water (27.1%), the second priority is attractiveness (13.1%), the third priority is environmental conditions (11.3%), the second priority is accommodation (7.6%). %), and the last priority is the relationship with other tourists (7.6%). The consistency index (MRC) was 82.4%, the selection index (Psi) was 11.1%, the eigenvalue was 12.981, and the consistency ratio (CR) was 0.37. Specific alternative management strategies include: Involving community groups, educational institutions and youth organisations around the Tagalaya village location to improve accommodation facilities, environmental conditions and tourist attractions in the mangrove forest area.
Keywords: Hutan; Mangrove; Ekologi; Ekowisata; Tagalaya